Genetic Rodent Models of Amyotrophic Lateral Sclerosis. (2nd January 2011) - Van Den Bosch, L.
Abstract : Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by the selective death of motor neurons in the motor cortex, brainstem, and spinal cord. A large number of rodent models are available that show motor neuron death and a progressive motor phenotype that is more or less reminiscent of what occurs in patients. These rodent models contain genes with spontaneous or induced mutations or (over) express different (mutant) genes. Some of these models have been of great value to delineate potential pathogenic mechanisms that cause and/or modulate selective motor neuron degeneration. In addition, these genetic rodent models play a crucial role in testing and selecting potential therapeutics that can be used to treat ALS and/or other motor neuron disorders. In this paper, we give a systematic overview of the most important genetic rodent models that show motor neuron degeneration and/or develop a motor phenotype. In addition, we discuss the value and limitations of the different models and conclude that it remains a challenge to find more and better rodent models based on mutations in new genes causing ALS.